Risk Stratification for Organ/Space Surgical Site Infection in Advanced Digestive System Cancer - Sun, Chen; Gao, Hui; Zhang, Yuelun; Pei, Lijian; Huang, Yuguang (Frontiers in Oncology, 2021)
Background Organ/space surgical site infection (organ/space SSI) is a serious postoperative complication, closely related to a poor prognosis. Few studies have attempted to stratify the risk of organ/space SSI for patients with advanced digestive system cancer. This study aimed to identify a simple risk stratification for these patients based on perioperative factors. Methods The study was based on two randomized controlled trials (RCT) (NCT02715076, ChiCTR-IPR-17011099), including 839 patients undergoing elective radical resection of advanced digestive system cancer. The primary outcome was organ/space SSI within 30 days after surgery. Multivariable logistic regression model was used to identify risk factors. The risk of organ/space SSI stratified over those risk factors was compared using chi-square tests and the relative risk (RR) was estimated. Results Among the 839 patients, 51 developed organ/space SSI (6.1%) within 30 days after surgery. According to the multivariable logistic regression model, 3 procedure types, including gastrectomy (OR=8.22, 95% CI: 2.71-24.87, P<0.001), colorectal resection (OR=8.65, 95% CI: 3.13-23.85, P<0.001) and pancreatoduodenectomy (OR=7.72, 95% CI: 2.95-20.21, P<0.001), as well as anaesthesia time > 4 h (OR=2.38, 95% CI: 1.08-5.27, P=0.032) and prolonged ICU stay (OR=4.10, 95% CI: 1.67-10.10, P=0.002), were risk factors for postoperative organ/space SSI. The number of risk factors was significantly associated with an increased risk of organ/space SSI (P<0.001), which was 2.8% in patients with 0-1 risk factor (RR=0.20, 95% CI: 0.11-0.35), 13.0% in patients with 2 risk factors (RR=3.64, 95% CI: 2.14-6.20) and 35.7% in patients with 3 risk factors (RR=6.41, 95% CI: 3.01-13.65). Conclusion This study is a preliminary exploratory and provides a simple risk stratification to identify the risk of postoperative organ/space SSI for patients with advanced digestive system cancer. Further research is needed to validate and generalize the results in a wider population. Clinical Trial Registration ClinicalTrials.gov, identifier NCT02715076; Chinese Clinical Trial Registry [https://www.chictr.org.cn/enindex.aspx], identifier ChiCTR-IPR-17011099.